The Role of Work Motivation, Workload, and Competency in Influencing Employee Performance through Job Satisfaction - Thifa Amani Prahasyila; Justine Tanuwijaya; Andreas Wahyu Gunawan (Jurnal Syntax Transformation, 2024)
In a dynamic and competitive financial industry, employee performance (performance) plays a key role in determining the success and growth of the organisation. This study aims to analyse the effect of work motivation, workload, and competency on job satisfaction, and its impact on performance in the financial industry in Jakarta.  This research uses quantitative methods by distributing questionnaires to employees in the financial industry in Jakarta. The data collected was then analysed using regression analysis to test the effect of independent variables on the dependent variable. The results showed that work motivation, workload, and competency have a significant effect on job satisfaction. Furthermore, job satisfaction was also found to have a significant effect on employee performance. These findings confirm the importance of paying attention to these factors in improving employee performance in the financial industry. Organisations need to develop effective strategies and policies to increase work motivation, manage workload, and develop employee competencies. By paying attention to these factors, it is expected to increase job satisfaction and ultimately improve employee performance in the highly competitive financial industry. This study concludes that work motivation, workload, and competency have a significant effect on job satisfaction, which in turn has an impact on improving employee performance in the financial industry. The findings provide practical implications for organisations to pay attention to these factors in an effort to improve employee performance.